Legal Protection for Consumers and Organizers in Organizing Non-Bank International Money Transfers (Cross Border Remittance) - Ade Rizki Saputra; Mira Gunati; Ryan Faisal (Formosa Journal of Sustainable Research, 2024)
This research investigates the regulatory and supervisory system for non-bank international remittance service providers within the applicable legal framework. Through a descriptive-analytical approach, this research explores legal protection mechanisms for consumers and the role of government institutions in ensuring compliance and protection of consumer interests and market stability. Data was collected through analysis of regulatory documents, literature, and interviews with experts in the financial industry. The research findings highlight challenges in implementing regulations, a lack of consumer awareness, and the need for technological innovation to strengthen monitoring and reporting of financial transactions. Recommendations include strengthening international cooperation, consumer education, strengthening compliance and law enforcement, technological innovation, and collaboration with industry